DORA in practice - Ruud, Kenneth (Septentrio Conference Series, 2021)
See RECORDING. Although the San Fransisco Declaration of Research Assessment (DORA) provides guidelines for best practice in research assessment, many institutions and reviewers at first find it difficult to ensure that the guidelines are adopted in their own evaluation committees and evaluation work. In this talk, I will share some suggestions for how institutions can ensure that the DORA guidelines are used by their evaluation committees. Based on personal experience as a chair of review panel for organizations that have signed the DORA declaration, I will also share some experiences on how one as chair may facilitate the use of the DORA best practice in evaluation work, as well as how this influences the evaluation process.